Lessons learned: program messaging in gender-transformative work with men and boys in South Africa - Amanda P. Viitanen; Christopher J. Colvin (Taylor & Francis Group, 2015)
Background: Adherence to traditional notions of masculinity has been identified as an important driver in the perpetuation of numerous health and social problems, including gender-based violence and HIV. With the largest generalized HIV epidemic in the world and high rates of violence against women, the need for gender-transformative work in South Africa is broadly accepted in activist circles and at the national and community level. Because of the integral role men play in both of these epidemics, initiatives and strategies that engage men in promoting gender equality have emerged over the last decade and the evidence base supporting the effectiveness of masculinities-based interventions is growing. However, little research exists on men's receptivity to the messages delivered in these programs. Objective: This article examines the current practices among a set of gender-transformation initiatives in South Africa to see what lessons can be derived from them. We look at how South African men participating in these programs responded to three thematic messages frequently found in gender-transformative work: 1) the 'costs of masculinity' men pay for adherence to harmful gender constructs; 2) multiple forms of masculinity; and 3) the human rights framework and contested rights. Design: This article synthesizes qualitative findings from in-depth interviews, focus group discussions, and ethnographic research with men participating in several gender- and health-intervention programs in South Africa. The data were collected between 2007 and 2011 and synthesized using some of the basic principles of meta-ethnography. Results and conclusions: Overall, men were receptive to the three thematic messages reviewed; they were able to see them in the context of their own lives and the messages facilitated rich dialog among participants. However, some men were more ambivalent toward shifting gender notions and some even adamantly resisted engaging in discussions over gender equality. More research is needed to gauge the long-term impact of participation in interventions that target gender and health.